Evaluation of a comprehensive school physical activity program: Be a Champion!. (August 2019) - Singletary, Camelia R.; Weaver, Glenn; Carson, Russell L.; Beets, Michael W.; Pate, Russell R.; Saunders, Ruth P.; Peluso, Alexandra G.; Moore, Justin B.
Highlights: CSPAP implementation requires buy-in from administrators, teachers, staff, students, and community members who have a vested interest. Begin with evaluation of student activities, staff and community involvement, and the policies/environments of individual schools. Policies and practices related to before-and after-school activities should focus on training of leaders to adapt to student wants and needs. Classroom time can be used to increase movement with integration of PA into academic lesson plans. Diversify activities and equipment during times when students have opportunities to engage in sustained moderate-to-vigorous PA. Abstract: Background: Comprehensive School Physical Activity Programs (CSPAPs) are widely supported to increase physical activity (PA) in schools, but little has been reported to inform a comprehensive evaluation effort. The purpose of this report is to describe a comprehensive evaluation and monitoring strategy for CSPAP implementation. Methods: The System for Observing Staff Promotion of Activity and Nutrition (SOSPAN), System for Observing Student Movement in Academic Routines and Transitions (SOSMART), and System for Observing Play and Leisure Activity (SOPLAY) were employed to record student and staff behaviors (2642 total scans). To assess policies, practices, and environments, a CSPAP Policies and Practices questionnaire was used, which included components of the School Health Index, the School PA Policy Assessment, the School Environment and Policies Survey, and the School Health Policies and Practices Study. Youth PA (minutes/day) was assessed using accelerometers. Results: Working with school sites to ascertain the number of opportunities that are provided for PA and the amount of PA students engage in is challenging but feasible. The use of systematic observation, accelerometers, and questionnaires can provide a comprehensive representation of policies, practices, and behaviors to aid in establishing targeted PA action items. Conclusions: Developing an evaluation framework that was rigorous enough to assess the physical, social, and policy environment of a school in order to answer the overarching research questions of the study but flexible enough to be feasibly streamlined for utilization by a school implementation team proved to be challenging but possible.